Materialism, Self-Objectification, and Capitalization of Sexual Attractiveness Increase Young Chinese Women’s Willingness to Consider Cosmetic Surgery - Sun, Qingqing (Frontiers in Psychology, 2018)
Research reveals significant positive associations between materialism and cosmetic surgery consideration, yet little is known about why this relationship exists. To address this question, the present study examined potential mediators of the links between materialism and cosmetic surgery consideration. A sample of 336 Chinese undergraduate women completed measures of materialism, self-objectification, capitalization of sexual attractiveness, and cosmetic surgery consideration. Correlational analysis showed that materialism, self-objectification, and capitalization of sexual attractiveness were significantly positively correlated with cosmetic surgery consideration. The results of path analyses revealed that higher materialism predicted more willingness to consider cosmetic surgery, both directly and indirectly via higher self-objectification and capitalization of sexual attractiveness.